Multifaceted roles and regulation of nucleotide-binding oligomerization domain containing proteins - Dixon, Charneal L.; Wu, Amy; Fairn, Gregory D. (Frontiers in Immunology, 2023)
Nucleotide-binding oligomerization domain-containing proteins, NOD1 and NOD2, are cytosolic receptors that recognize dipeptides and tripeptides derived from the bacterial cell wall component peptidoglycan (PGN). During the past two decades, studies have revealed several roles for NODs beyond detecting PGN fragments, including activation of an innate immune antiviral response, NOD-mediated autophagy, and ER stress induced inflammation. Recent studies have also clarified the dynamic regulation of NODs at cellular membranes to generate specific and balanced immune responses. This review will describe how NOD1 and NOD2 detect microbes and cellular stress and detail the molecular mechanisms that regulate activation and signaling while highlighting new evidence and the impact on inflammatory disease pathogenesis.